Transforming Future Educators: The Impact of Service-Learning on Pre-Service Teachers' Professional Development at an Orphanage in North Jakarta - Lawasi, Miryam Caroline; Sadewa, Melodika Paku; Hulu, Nadia Nindisari; Setya, Enoch Gratia Pesah; Sihombing, Michael Recard (ICONELT, 2024)
Service-learning is a powerful tool for pre-service teachers' development. This approach integrates academic learning with real-world practice, developing not only content knowledge but also the essential 21st-century skills needed for effective teaching. This study explores how pre-service teachers in Indonesia view service-learning implemented at an orphanage in North Jakarta. Questionnaires will be used to understand how they see the integration of service-learning into their class activity and its impact on developing skills like critical thinking, collaboration, and cultural awareness. Focusing on the unique context of an orphanage, this research delves into both potential benefits and challenges that pre-service teachers might experience when using service-learning in this setting. Furthermore, the study seeks to contribute to a deeper understanding of how service-learning in a specific community can transform pre-service teachers’ professional development, equipping them with the skills and experiences for success in later classrooms.